Beef and cone-in-cone calcite fibrous cements associated with the end-Permian and end-Triassic mass extinctions: Reassessment of processes of formation - Kershaw, S; Guo, L (Journal of Palaeogeography, 2015)
This paper is a contribution to IGCP630. This paper reassesses published interpretation that beef and cone-in-cone (B-CIC) fibrous calcite cement were precipitated contemporaneously just below the sea floor in unconsolidated sediment, in limestones associated with the end-Permian (P/T) and end-Triassic (T/J) mass extinctions. That interpretation introduced the concept of a sub-seafloor carbonate factory associated with ocean acidification by raised carbon dioxide driven by volcanic eruption, coinciding with mass extinction. However, our new fieldwork and petrographic analysis, with literature comparison, reveals several problems with this concept. Two key points based on evidence in the T/J transition of UK are: A) that B-CIC calcite deposits form thin scattered layers and lenses at several horizons, not a distinct deposit associated with volcanic activity; B) B-CIC calcite is more common in Early Jurassic sediments after the extinction and after the end of the Central Atlantic Magmatic Province volcanism proposd to have supplied the carbon dioxide required. Our samples from Late Triassic, Early Jurassic and Early Cretaceous limestones in southern UK show that B-CIC calcite occurs in both marine and non-marine sediments, therefore ocean processes are not mandatory for its formation. There is no proof that fibrous calcite was formed before lithification, but our Early Jurassic samples do prove fibrous calcite formed after compaction, thus interpretation of crystal growth in unconsolidated sediment is problematic. Furthermore, B-CIC crystals mostly grew both upwards and downwards equally, contradicting the interpretation of the novel carbonate factory that they grew preferentially upwards in soft sediment. Finally, Early Jurassic and Early Cretaceous examples are not associated with mass extinction. Three further key points derived from literature include: A) B-CIC calcite is widespread geographically and stratigraphically, not clustered around mass extinctions or the PETM event; B) isotope signatures suggest ...